2016
DOI: 10.1038/tp.2016.146
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in amygdala–prefrontal circuits in infants exposed to prenatal maternal depression

Abstract: Prenatal exposure to maternal depression is common and puts offspring at risk for developing a range of neuropsychiatric disorders. Despite its prevalence and adverse associations, neurobiological processes by which prenatal maternal depression (PMD) confers risk remain poorly understood. Maternal mood and fetal behavior were assessed between 34 and 37 gestational weeks. Using resting-state functional magnetic resonance imaging (fMRI) and diffusion MRI, we examined functional and structural connectivity within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
161
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(173 citation statements)
references
References 47 publications
(52 reference statements)
10
161
2
Order By: Relevance
“…Rifkin-Graboi et al, (2013) reported that prenatal depression is associated with reduced microstructure, but not with the volume of the right amygdala in newborn infants. Altered functional connectivity of the amygdala was also reported by Posner et al (2016). Altered functional connectivity of the amygdala was also reported by Posner et al (2016).…”
mentioning
confidence: 80%
“…Rifkin-Graboi et al, (2013) reported that prenatal depression is associated with reduced microstructure, but not with the volume of the right amygdala in newborn infants. Altered functional connectivity of the amygdala was also reported by Posner et al (2016). Altered functional connectivity of the amygdala was also reported by Posner et al (2016).…”
mentioning
confidence: 80%
“…Prenatal exposure to maternal psychological stress, such as depression and anxiety, has been associated with alterations in child neurodevelopment and stress regulation systems (Sandman, Class, Glynn, & Davis, ; Van den Bergh et al., ). Changes in offspring hypothalamic–pituitary–adrenal axis function and glucocorticoid receptor sensitivity (Frasch et al., ; Loman & Gunnar, ), as well as alterations in brain functional and structural development (e.g., cortical thinning, amygdala‐prefrontal connectivity), and related problems in attention and emotion regulation have been reported (Dunkel Schetter & Tanner, ; Posner et al., ; Sandman, Glynn, & Davis, ; Sandman, Class, et al., ). Moreover, higher rates of symptoms of depression and anxiety as well as attention deficit hyperactivity disorder and conduct disorders have been reported in children with prenatal stress (PS) exposure (Glover, , ; Van den Bergh et al., ).…”
Section: The Present Studymentioning
confidence: 99%
“…Electronic mail may be sent to eeva-leena.kataja@utu.fi. Gunnar, 2010), as well as alterations in brain functional and structural development (e.g., cortical thinning, amygdala-prefrontal connectivity), and related problems in attention and emotion regulation have been reported (Dunkel Schetter & Tanner, 2012;Posner et al, 2016;Sandman, Class, et al, 2016). Moreover, higher rates of symptoms of depression and anxiety as well as attention deficit hyperactivity disorder and conduct disorders have been reported in children with prenatal stress (PS) exposure (Glover, 2011(Glover, , 2015Van den Bergh et al, 2017).…”
mentioning
confidence: 99%
“…We focused on the amygdala that has featured prominently in developmental studies examining the influence of maternal mental health. Prenatal maternal depressive symptoms associate with the amygdala microstructure of neonates (Rifkin‐Graboi et al, ) and with amygdala functional connectivity with the prefrontal and limbic cortex as well as with the sensory cortex in infants (Posner et al, ; Qiu et al, ). Moreover, 10‐year‐old children of mothers with postnatal depression show larger bilateral amygdala volumes compared with those of mothers without depression (Lupien et al, ).…”
Section: Introductionmentioning
confidence: 99%